Iron Dysregulation and Dormant Microbes as Causative Agents for Impaired Blood Rheology and Pathological Clotting in Alzheimer’s Type Dementia - Pretorius, Lesha; Kell, Douglas B.; Pretorius, Etheresia (Frontiers in Neuroscience, 2018)
AAlzheimer’s disease and other similar dementias are debilitating neurodegenerative disorders whose aetiology and pathogenesis remain largely unknown, even after decades of research. With the anticipated increase in prevalence of Alzheimer’s disease among the more susceptible ageing population, the need for disease-modifying treatments is urgent. While various hypotheses have been put forward over the last few decades, we suggest that sporadic Alzheimer’s disease is triggered by external environmental factors, co-expressing in individuals with specific genetic susceptibilities. These external stressors are defined in the Iron Dysregulation and Dormant Microbes (IDDM) hypothesis, previously put forward. This hypothesis is consistent with current literature in which serum ferritin levels of individuals diagnosed with Alzheimer’s disease are significantly higher compared those of age- and gender-matched controls. While iron dysregulation contributes to oxidative stress, it also causes microbial reactivation and virulence of the so-called dormant blood (and tissue) microbiome. Dysbiosis (changes in the microbiome) or previous infections can contribute to the dormant blood microbiome (atopobiosis), and they also directly promote systemic inflammation via the amyloidogenic formation and shedding of potent inflammagens such as lipopolysaccharides. The simultaneous iron dysregulation and microbial aberrations affect the haematological system, promoting fibrin amylodiogenesis and pathological clotting. Systemic inflammation and oxidative stress can contribute to blood brain barrier permeability and the ensuing neuro-inflammation, characteristic of Alzheimer’s disease. While large inter-individual variability exists, especially concerning disease pathogenesis, the IDDM hypothesis acknowledges primary causative factors which can be targeted for early diagnosis and/or for prevention of disease progression.